2020
DOI: 10.1155/2020/8814290
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Persistent Postoperative Pain in Patients with Hip Fractures

Abstract: Osteoporotic fractures are common among older people, and hip fractures (HF) can be devastating. Surgery is indicated for most cases of HF, and chronic persistent postoperative pain is likely to occur. This study investigated the multifaceted factors related to persistent pain occurring during the acute phase and subacute phase of recovery after HF surgery. We conducted a prospective 8-week study of older HF patients after surgery. We evaluated pain intensity, depression symptoms, the fear of falling, pain cat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 34 publications
0
12
0
1
Order By: Relevance
“…In Cristancho et al [ 59 ], researchers found that a group experiencing a persistently high level of depressive symptoms had poorer functional recovery and higher rates of pain in the year following hip fracture. However, there are new experimental data[ 60 ] showing that the relationship between pain and the geriatric depression scale (GDS) after hip fracture is not statistically significant. The effect of depression on postoperative pain needs to be further determined.…”
Section: Resultsmentioning
confidence: 99%
“…In Cristancho et al [ 59 ], researchers found that a group experiencing a persistently high level of depressive symptoms had poorer functional recovery and higher rates of pain in the year following hip fracture. However, there are new experimental data[ 60 ] showing that the relationship between pain and the geriatric depression scale (GDS) after hip fracture is not statistically significant. The effect of depression on postoperative pain needs to be further determined.…”
Section: Resultsmentioning
confidence: 99%
“…Acute pain severity is associated with an increased risk of persistent pain prevalence at varied time points after surgery. Among 72 elderly patients who underwent surgery for hip fractures, pain with movement assessed 2 and 4 weeks after surgery was significantly associated with persistent pain at 8 weeks after surgery [ 19 ]. Similarly, severe acute postoperative pain after Cesarean section has been associated with the development of CPSP [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, to ensure transparency, the authors have included both variables as we have done in our previously published studies [ 25 , 26 ]. The 15-item GDS and FIM were used to determine the depression symptoms and the generic ability to perform ADL, respectively [ 27 , 28 ]. Breakpoints of 8 g/dL, 10 g/dL, and 12 g/dL were used to classify the Hb level at admission.…”
Section: Methodsmentioning
confidence: 99%